Understanding farmer seed systems in Sespond, North West Province - Kganyago, Mpho Clementine (University of Cape Town, 2020)
Farmer-led seed systems (FSS) provide the backbone for small-scale farmers and many rural communities that use traditional methods of farming to produce seeds that grow and adapt to local conditions. FSS differ from one community and farmer to the next, depending on the methods and practices used to maintain seed varieties. Seed diversity can enhance FSS by improving livelihoods and strengthening farmers' networks, thus contributing to resilient communities. Although nuanced, the dualistic agricultural system in South Africa consists largely of subsistence (small-scale) and commercial (large-scale) farming and includes different crop management systems and post-harvest practices. In South Africa, maize (Zea mays) is a major staple grain crop with a significant role as animal and poultry feed. The North West region is one of the highest white-maize-producing provinces in South Africa. Maize seed systems include both traditional, openpollinated varieties (OPVs) and cultivars such as modern hybrids and genetically modified (GM) seed varieties, including those engineered for specific purposes. The dominant GM maize is that designated for pest resistance using Bacillus thuringienesis (Bt), a soil bacterium which produces a toxin that is fatal to a wide variety of insects such as moths and flies. Many small-scale farmers prefer their own traditional seeds for breeding, planting, selection, selling and consuming. However, FSS based on traditional varieties are threatened by modern cultivars which may be introduced in different ways including through seed exchange, purchasing at shops or by pollination from nearby commercial farms. This study was conducted in the Sespond community of the North West Province. The aim of the study was to understand how small-scale farmers in Sespond maintain traditional maize varieties through selection and storage in a complex agricultural landscape that incorporates both formal and informal seed systems. The formal system represents industrialised farms and companies that work with commercial seed. The informal system represents small-scale farmers who rely on their own seed. Qualitative methods included mapping software which was used to obtain visual agricultural data in and around Sespond. Semi-structured interviews were conducted with 30 small-scale farmers to collect information about their farming practices, including the maize varieties planted. Quantitative methods included collecting 20 maize samples from different farmers for genetic analysis. Agdia® immunostrip tests were used to detect for the presence of Crystal protein (Cry protein) produced by the Bt bacterium, engineered to improve the resistance of maize against insects. The results showed that 13 samples were negative for the protein and seven samples were positive for the protein. A key finding is that small-scale farmers are not able to detect the different maize varieties in their seed systems. This represents a threat for traditional seed varieties in the community as without this knowledge, farmers are not able to adequately manage their production and storage systems. Farmers made use of alternative storage methods such as the mill to reduce seed damage they experienced at home. However, the findings of this research showed that there was an increasing risk of farmers' traditional maize being mixed with GM maize at the mill. Farmers' rights to plant and consume traditional maize were therefore undermined. This study recommends that (a) efforts are made to increase awareness among farmers that help to distinguish transgenes from hybrids and traditional maize varieties; (b) measures are implemented at mills to both improve the transparency about the storage and processing of traditional maize and to separate traditional maize from hybrid and GM maize.